2019
DOI: 10.21276/ijcmr.2019.6.11.13
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Usage and Type of Topical Anesthesia among Dentists of Tricity

Abstract: Introduction: Local anaesthesia injection is widely accepted as the gold standard for pain management during various dental procedures. Intra-oral topical anaesthesia not only reduces the pain of injection prick but also several minor dental procedures can be carried out under topical anaesthetic. Study aimed to determine the usage, type & effectiveness of various topical anaesthetics used for minor dental procedures in pediatric patients. Material and Methods: A self-structured, closed ended questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…Crout et al [14] avaliou a eficácia dos anestésicos locais usados e descobriu que o EMLA é muito eficaz como creme tópico intraoral, apesar disso, o gel foi a forma de apresentação mais utilizada pelos entrevistados do presente estudo, com 89%, enquanto que em uma pesquisa realizada por Dhindsa [15], essa porcentagem cai para 58%.…”
Section: Results (Review)unclassified
“…Crout et al [14] avaliou a eficácia dos anestésicos locais usados e descobriu que o EMLA é muito eficaz como creme tópico intraoral, apesar disso, o gel foi a forma de apresentação mais utilizada pelos entrevistados do presente estudo, com 89%, enquanto que em uma pesquisa realizada por Dhindsa [15], essa porcentagem cai para 58%.…”
Section: Results (Review)unclassified
“…Among the dentists who never used topical anesthesia in children, the indicated reason was the perception that it was not effective. Previous research by Kohli et al [ 19 ] and Dhindsa et al [ 21 ] reported that 1% and 2% of respondents, respectively, perceived topical anesthesia to be ineffective. The lack of effectiveness can be attributed to the different factors that govern the clinical efficacy of topical anesthetics such as anesthetic's type, formulation, and concentration used, as well as the duration and site of application [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample calculations were performed with the sample size calculator V 2.0 using a single proportion formula based on data from previous relevant research [ 20 , 21 ]; (proportion ( p ) = 86%, precision = 10%, alpha error = 0.05, power = 0.8). The minimum sample size required was 47.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations